PENERAPAN METODE INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI POKOK BAHASAN TUMBUHAN HIJAU - Muhammad Thoifur Ibnu Fajar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2020)
Low motivation to learn biology and the ability of students to be uneven causes low biology learning outcomes for class VIII C students of SMP Negeri 2 Maesan Bondowoso. The results of the interview, the average value of learning completeness in biology under KKM 70 and classical completeness is 85%. Classroom action research was carried out in two cycles and subject matter samples of green plants through guided inquiry methods to improve biology learning outcomes for class VIII C students of SMP Negeri 2 Maesan Bondowoso, totaling 30 students. The data obtained were homework tests and daily tests of multiple choice questions to determine cognitive learning outcomes, affective observation sheets to observe student activity and psychomotor observation sheets to determine students' skill abilities. Data were analyzed using qualitative and quantitative analysis. The results of the study, the first cycle of cognitive learning outcomes is still below the KKM 63.33%, affective learning outcomes are quite active 67.40% and psychomotor learning outcomes are more active 78.88%. The second cycle of cognitive learning outcomes has been completed above KKM 86.66%, affective learning outcomes 85.92% and psychomotor 86.29% very active after an evaluation of the first cycle, motivating before starting the material, explaining the material, guided inquiry stages and assignments in more detail, guiding students in an orderly manner, meticulously working on assignments and having fun interactions to create a comfortable learning atmosphere. The second cycle was stopped after the three mean cognitive, affective and psychomotor scores had met the minimum completeness criteria.